2019
DOI: 10.1021/acsami.9b01553
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effects Determine the Selectivity of Planar Au–Cu Bimetallic Thin Films for Electrochemical CO2 Reduction

Abstract: Au–Cu bimetallic thin films with controlled composition were fabricated by magnetron sputtering co-deposition, and their performance for the electrocatalytic reduction of CO2 was investigated. The uniform planar morphology served as a platform to evaluate the electronic effect isolated from morphological effects while minimizing geometric contributions. The catalytic selectivity and activity of Au–Cu alloys was found to be correlated with the variation of electronic structure that was varied with tunable compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 51 publications
4
73
1
Order By: Relevance
“…59 Such shift results in a weakening of the binding strength of *CO due to the occupancy of antibonding states. 18,60 Therefore, product selectivity in the Zn-rich CuZn NPs seems to be controlled by the ligand effect rather than strain effects, leading to the loss of the functionality of the Cu site for further reduction of CO intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…59 Such shift results in a weakening of the binding strength of *CO due to the occupancy of antibonding states. 18,60 Therefore, product selectivity in the Zn-rich CuZn NPs seems to be controlled by the ligand effect rather than strain effects, leading to the loss of the functionality of the Cu site for further reduction of CO intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…The switch in the catalytic behavior of this system was explained in refs ( 25 and 111 ) by the interplay of geometric and electronic effects. The expansion of the interatomic distances was found to result in a more favorable stabilization of the reaction intermediates, leading to the formation of products beyond *CO. 319 Furthermore, changes in the electronic structure due to Cu and Zn alloying resulted in a shift of the d -band center of Cu away from the Fermi level, 438 and a weakening of the *CO binding 111 , 439 , 440 during the gradual Cu and Zn reduction and alloying, leading to different catalytic selectivity and stability for Cu-rich and Cu-poor samples. In fact, it was suggested that the Cu-M interatomic distances might constitute a convenient descriptor of the catalyst properties in these bimetallic NPs, with NPs with shorter interatomic distances (similar to that in metallic Cu) favoring the production of CH 4 , while NPs with longer Cu—M distances favor the production of CO.…”
Section: Examplesmentioning
confidence: 99%
“…By combining these metals with Cu to form alloy or bimetallic structures, the CO 2 RR activity was increased. While previous works using these alloyed nanoparticles further improved the selectivity and activity of CO 2 RR toward CO at lower overpotential, [ 80,128 ] bimetallic structures have shown promising synergistic effects that lead toward the CC coupling reaction. Based on a previous report by Kuhl et al about the electrocatalytic conversion of CO 2 using several transition metal surfaces, including Au, Ag, Zn, Cu, Ni, Pt, and Fe, it was revealed that Cu may not be the only metal that has the ability to catalyze hydrocarbon and alcohol formation.…”
Section: Surface Structure‐dependent Catalytic Activity/selectivity Omentioning
confidence: 99%